MULTIDISCIPLINARY APPROACH TO PREVENTION OF VIOLENCE IN PRESCHOOL INSTITUTIONS - Dedaj, Marta (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2016)
The goal of this paper is to present the most important issues with respect to violence prevention in preschool institution. The role of humanisti-oriented padagogy is to find, through preventive programmes, appropriate and timely responses to the occurrence of violence against children and among children. The question is: “How come some children, despite numerous negative factors making their life in the community difficult, still do not “go astay” and how can these skills be learnt?“. The author embraces the model of resilience as a dynamic interaction between certain bio-psycho-social  characteristics of an individual and broader social context. Greater efficiency of prevention programmes would be achieved if protection factors were perceived in interaction with risk factors. We can conclude that prevention programmes should be based on multidisciplinary approach and cooperation of experts from different systems.
Keywords: approach; Multidisciplinary; children; violence; prevention